Comparison of Embryo Production between Simmental and Limousin Cattle in Different Seasons at Cipelang Cattle Embryo Center - Robbaani, Muhammad; Nurlayasari, Irma; Khaeruddin, Khaeruddin; Wahjuningsih, Sri (Tarjih Tropical Livestock Journal, 2024)
Indonesia is a tropical country that has two different seasons, namely the rainy season and the dry season. Embryo production can be influenced by several factors, one of which is the season factor. Seasonal factors can affect the quality and quantity of embryos produced. The purpose of this study was to determine the comparison of embryo production of Simmental cattle with Limousin cattle in the rainy season and the dry season. The material used was 40 donor cattle divided into 20 Simmental cattle and 20 Limousin cattle aged 3 to 6 years with a body weight of 450-700 kg. The research procedure starts from superovulation using reproductive hormone injection, artificial insemination, embryo collection using flushing technique and embryo evaluation. The research method used was a case study. Data processing and analysis in this study used the independent t-test with research variables of the number of embryos collected, the quality of embryos produced, the number of corpus luteum produced, the level of response, and the level of recovery. The results of this study were no significant difference (P> 0.05) in the production of Limousin and Simmental cattle embryos in the rainy season. In contrast to the dry season, the results were (P <0.05) which means there is a difference in the production of Limousin and Simmental cattle embryos in the dry season. On the other hand, Limousin cattle showed that Limousin cattle were slightly superior to all variables in the dry season.